2013
DOI: 10.1159/000345698
|View full text |Cite
|
Sign up to set email alerts
|

Reports of Patients and Relatives from the CogniCIS Study about Cognition in Clinically Isolated Syndrome: What Are Our Patients Telling Us?

Abstract: Objective: To assess the Multiple Sclerosis Neuropsychological Questionnaire (MSNQ) in patients with clinically isolated syndrome (CIS). Methods: 130 European CIS patients and 60 relatives completed the MSNQ. Results: The mean (SD) MSNQ score for CIS patients was 15.5 (10.8) and for their informants 11.3 (9.6). Neither the CIS patient nor relative MSNQ report scores correlated with any of the cognitive test scores in the Brief Repeatable Battery of Neuropsychological Tests, but they were significantly related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 75 publications
0
5
0
1
Order By: Relevance
“…In patients with MS, increased neuropsychiatric symptoms and decreased HRQoL have been related to more pronounced clinical disability and cognitive dysfunction since the early stages and this relation was stronger with increasing severity of the disease [ 11 , 18 , 35 , 36 ]. In patients with CIS, a single study found association between self-perceived cognitive functioning and increased depressive symptoms, but did not study association with HRQoL [ 37 ]. Associations of clinical disability with neuropsychiatric symptoms and HRQoL have not been studied in patients with CIS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with MS, increased neuropsychiatric symptoms and decreased HRQoL have been related to more pronounced clinical disability and cognitive dysfunction since the early stages and this relation was stronger with increasing severity of the disease [ 11 , 18 , 35 , 36 ]. In patients with CIS, a single study found association between self-perceived cognitive functioning and increased depressive symptoms, but did not study association with HRQoL [ 37 ]. Associations of clinical disability with neuropsychiatric symptoms and HRQoL have not been studied in patients with CIS.…”
Section: Discussionmentioning
confidence: 99%
“…For identification of psychiatric disorders in the participants we used the unstructured clinical interview and medical records unlike the structured diagnostic interview, which would determine whether the patients with CIS may fulfil criteria for mental health disorders. Cognitive functioning was evaluated by a self-report questionnaire and a single neuropsychological test, which may not properly reflect the general cognitive status [ 37 ]. Experimental brain MRI was available only in a subset of healthy control participants.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, self-reported questionnaires about cognition in MS, might be useful in clinical studies but may not provide enough information about the cognitive domains affected to the examiner [ 59 ]. For example, the patient reported Multiple Sclerosis Neuropsychological Questionnaire (MSNQ-P) score may correlate with depression and anxiety but not with scores of cognitive tests [ 60 , 61 ]. However, the informant version of the MSNQ (MSNQ-I) seems to describe more accurately the cognitive profile of an MS patient [ 62 ], thus indicating that it could be used as an alternative method for the preliminary evaluation of cognitive function in MS patients.…”
Section: How To Measure?mentioning
confidence: 99%
“…Eleven CIS studies used five different instruments to assess depressive symptoms (Appendix 3) [44,60,69,[61][62][63][64][65][66][67][68]. The most frequently used questionnaire was BDI, which allowed for a meta-analysis of four studies (Table 2).…”
Section: Cismentioning
confidence: 99%